Treatment outcome of mineral trioxide aggregate in open apex teeth - Mente, Johannes; Leo, Meltem; Panagidis, Dimos; Ohle, Marc; Schneider, Sven; Lorenzo Bermejo, Justo; Pfefferle, Thorsten (Journal of endodontics, 2013)
Introduction - This cohort study is the second phase of a previously reported trial. The primary aim was to assess the outcome of the treatment of teeth with open apices managed by the orthograde placement of mineral trioxide aggregate (MTA) apical plugs. The secondary goal was to identify potential outcome factors for this kind of treatment with a larger sample size and longer follow-up periods than in the first phase of the project. - Methods - Two hundred twenty-one patients who had been treated between 2000 and 2010 were contacted for follow-up examination 12-128 months after treatment (median, 21 months). At the time of treatment, these patients presented a total of 252 teeth with open apices caused by apical root resorption or excessive apical enlargement or with immature apices. Treatment was performed by supervised undergraduate students (12% of teeth), general dentists (49%), and dentists whose practice was limited to endodontics (39%). The investigated outcome relied on clinical and radiographic criteria and was dichotomized as healed or diseased. - Results - Of 252 examined teeth (88% recall rate), 90% were healed. Teeth with and without preoperative periapical radiolucencies demonstrated healed rates of 85% and 96%, respectively. Forty-five percent of the teeth (113/252) were followed up at least 2 years later and 21% (53/252) at least 4 years later. Univariate survival analyses identified 4 prognostic factors: preoperative apical periodontitis, the experience of the treatment providers, the number of treatment sessions, and the apical extrusion of MTA. Multiple regression analyses confirmed an increased risk of disease for teeth with preoperative apical periodontitis (hazard ratio = 4.59; 95% confidence interval, 1.57-13.4; P = .005). In addition, the experience of the treatment provider was found to influence the outcome (hazard ratio = 0.25; 95% confidence interval, 0.09-0.75; P = .03). - Conclusions - Orthograde placement of MTA apical plugs appears to be a promising treatment option for teeth with open apices. The healed rates for such teeth were high in this study, even after follow-up periods of more than 4 years. The presence of preoperative apical periodontitis was identified as an important prognostic factor.